Landscape-cognitive trail "To the mountain Vysoky Verkh" (National Park "Skole Beskids") - Burianyk, O. O.; Melnyk, A. V. (Journal of Education, Health and Sport, 2018)
The landscape diversity of the cognitive nature trail "To the mountain Vysoky Verkh" is characterized within the Skole Beskids National Nature Park, and nine landscape and cognitive stops are proposed that represent typical and unique landscape tracts, botanical, geological and hydrological objects, as well as cultural objects, and processes associated with the human economic activity. The trail begins and ends in the low-altitude landscape of the Dovzhkiv Landscape district of the Stryi-Sianky Verkhovyna and acquaints with the landscape tracts and the high terrain terraced bottom of the river valleys and the area of the hilly low mountains. Most of the trail is located in the Vysokyi Verkh landscape of Skole Beskids and represents the natural territorial complexes of the high-altitude terrain of steep midlands.